Pengaruh perencanaan pajak, aset pajak tangguhan, dan profitabilitas terhadap manajemen laba perusahaan industrial yang terdaftar di Bursa Efek Indonesia periode 2018-2022 - Sompotan, Kleef; Lambey, Robert; Kindangen, Wulan D. (Riset Akuntansi dan Portofolio Investasi, 2024)
This research aims to examine the influence of tax planning, deferred tax assets, and profitability on earnings management of industrial firms listed in the Indonesian Stock Exchange. Tax planning variables are measured by the RR index, deferred tax assets are measured by DTA, profitability is measured by ROA and earnings management is measured by SEC. This type of research is quantitative influence research using secondary data. The sampling technique used was non-probability sampling with a purposive sampling method and resulted in 32 companies as research samples from 63 companies. The data analysis technique in this research is multiple linear regression using the SPSS 29 program. The partial research results show that tax planning and deferred tax assets have a significant and positive effect on earnings management, and profitability has no effect on earnings management. The research results simultaneously show that tax planning, deferred tax assets, and profitability have an influence on earnings management.